Universities are better positioned to implement Community Based Breeding Program: Lessons from Ethiopian Universities - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (International Center for Agricultural Research in the Dry Areas, 2023)
Training of Training on Community Based Breeding Programs for Pastoral Areas Addis Abeba , Ethiopia